2011 Sept. 11 ten years from now - Ferguson, Niall (2001)
Take the long view. What will New York be like on Sept. 11, 2011? It's not difficult to imagine a rather wretched future. You need only visit one of those cities -- Jerusalem or Belfast -- that have been fractured by terrorism and religious strife to get a glimpse. Imagine a segregated city, with a kind of Muslim ghetto in an outer borough that non-Muslims can enter only -- if they dare -- with a special endorsement on their ID cards. Imagine security checkpoints at every tunnel and bridge leading into Manhattan, where armed anti terrorist troops check every vehicle for traces of explosives and prohibited toxins.